2020
DOI: 10.1111/jch.14099
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and stroke in Asia: A comprehensive review from HOPE Asia

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 79 publications
4
64
0
6
Order By: Relevance
“…Between 1990 and 2019, the number of incident stroke cases increased by approximately 70% worldwide [ 1 ]. In Asia, the incidence of stroke is around 116 to 483 per 100,000 individuals annually [ 2 ]. Particularly in Singapore, the incident of stroke cases increased from 5890 to 8849 between 2010 and 2019 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Between 1990 and 2019, the number of incident stroke cases increased by approximately 70% worldwide [ 1 ]. In Asia, the incidence of stroke is around 116 to 483 per 100,000 individuals annually [ 2 ]. Particularly in Singapore, the incident of stroke cases increased from 5890 to 8849 between 2010 and 2019 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that SBP was associated with stroke recurrence[ 25 ]. Turana et al [ 26 ] also found that SBP was positively correlated with stroke incidence, and adherence to hypertension treatment is to be the main goal in the prevention of stroke occurrence in several countries in Asia. In addition, in a cohort study, Zhuo et al [ 27 ] identified SBP as a risk factor for 2-year post-ischemic stroke recurrence prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is the fourth-largest cause of mortality, and, in the United States in 2018-2019, its primary types were ischemic infarction (87%), primary hemorrhage (10%), and subarachnoid hemorrhage (3%) [1]. On the other hand, Asians have a higher incidence of primary hemorrhage (25%) than Caucasians (10-17%), but the incidence of ischemic infarction increased in different countries of Asia (1.7-16%) during the period 2014-2017 [2]. Stroke incidence increases with age, and after 55 years, the incidence doubles with each subsequent decade; it is higher in men than women [1].…”
Section: Introductionmentioning
confidence: 99%
“…The increase is related to hyperglycemia, dyslipidemia, hypertension, and platelet aggregation with age, and their management prevents ischemic infarction. Ischemic infarction reduces the blood flow, resulting in a decrease in oxygen and nutrients, and it is treated by removing the clot [2]. The treatment delay develops neuronal cell death to induce adverse outcomes, such as vision problems, paralysis in the limbs, dizziness, confusion, and coordination loss due to blockage in the brain areas.…”
Section: Introductionmentioning
confidence: 99%